‘Only Stones and Stories Remain’: Greek American (Travel) Writing about Greece - Kindinger, Evangelia (Current Objectives of Postgraduate American Studies, 2012)
Since the early 1960s, numerous Greek American authors of the second and third generation have published personal accounts on their travels to Greece. In this paper, I argue that these authors adopt a double perspective, being both ‘visitors’ and ‘locals’ who are affiliated with both the ‘here’ and the ‘there.’ Returnees often experience a feeling of belatedness when arriving in their ancestral homeland. They overcome this feeling by inscribing themselves into the foreign but - paradoxically - familiar past, and by making a contribution to the Greek diaspora. Although the intersections of travel writing and return writing are strong, in this paper, return writing will be defined as a subgenre of both diaspora writing and travel writing.